Local Carpet Bombardment of Immobilized Cancer Cells With Hydrodynamic Cavitation - Gevari, Moein Talebian; Aydemir, Gizem; Gharib, Ghazaleh; Kutlu, Ozlem; Uvet, Huseyin; Ghorbani, Morteza; Kosar, Ali (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This study presents a method based on carpet bombardment of immobilized cells with cavitating flows. For this, immobilized cancer cell lines are exposed to micro scale cavitating flows from the tip of a micro nozzle under the effect of cavitation microbubbles. The deformation as a result of cavitation bubbles on exposed cells differs from one cell type to another. Therefore, the difference in cell deformation upon cavitation exposure (carpet bombardment) acts as a valuable indicator for cancer diagnosis. The developed system is tested on HCT-116 (Human Colorectal Carcinoma), MDA-MB-231 (Breast Adenocarcinoma), ONCO-DG-1 (Ovarian Adenocarcinoma) cell lines due to their clinical importance. The mechanical effects of cavitation are examined by considering the single-cell lysis effect (the cell membrane is ruptured, and the cell is destroyed) with the help of the Scanning Electron Microscopy (SEM) technique. Our study proposes a promising label-free method for the potential use in cancer diagnosis with cavitation bubble collapse, where microbubbles could be precisely controlled and directed to the desired locations, as well as the characterization of the biophysical properties of cancer cells. The proposed approach tool has the advantages of label-free approach, simple structure and low cost and is a substantial alternative for the existing tools.
Keywords: Cancer; Fluids; Hydrodynamics; Biomembranes; Scanning electron microscopy; Cells (biology); Surface morphology; Cancer diagnosis; hydrodynamic cavitation; spray structure; cavitation bubble; cancer cells; ULTRASOUND; Computer Science; Engineering; Telecommunications